Real-time data exchange using web service with CIM for aging estimation of distribution transformers - Ku, Te-Tien; Lin, Chia-Hung; Chen, Chao-Shun; Tsai, Kun-Lin; Zhang, Tong-Yu; Lee, Yih-Der; Cheng, Chin-Chan; Lin, Zi-Chun (Edelweiss Applied Science and Technology, 2024)
This paper applies web services using the common information model (CIM) to exchange measurement data from the transformer terminal unit (TTU) to the distribution management system (ADMS) for the aging estimation of distribution transformers. An application programming interface (API) is designed by using web services such as simple object access protocol (SOAP) and representational state transfer (RESTful) for TTU measurement data exchange. The structured query language (SQL) and the not only SQL (NoSQL) databases are used to store historical TTU data for neural network (NN) model training. An optimization architecture of web service with the database is proposed to increase data exchange performance. The exchanged real-time TTU data is input into a trained NN model that can provide a reference aging factor for the utility crew to balance distribution transformer loading. Finally, the graphic user interface (GUI) is designed in this paper to display real-time information and achieve asset management of distribution transformers.